IDENTIFICATION OF Leishmania tropica and Leishmania major BY REAL-TIME PCR USING ITS1 and KDNA GENES IN BAGHDAD - Nada Noori Younis; Amina N.AL-Thwani (Pakistan Journal of Biotechnology, 2018)
Cutaneous leishmaniasis (CL) is caused by Leishmania spp, this disease is a problem in Iraq. The purpose aims of the study is using a Qualitative - Real-time PCR (Q-R.T) to diagnosis compared with traditional methods to investigation of Leishmania species in Baghdad. Total 75 suspected patient with CL from both sex was enrolled in the present work study during the period between March / 2016 to March / 2017 who attended, AL-Yarmook, AL-Karamaa Al-Kadhimiya, Al-Kindi, Teaching Hospitals in Baghdad, all the demographic feature of the diseases, were recorded. The direct Microscopic examination was carried out by direct smears using Giemsa stain, aspiration fluid from lesions were cultured on Novy–MacNeal–Nicolle (NNN) medium and used R T-PCR for detection of internal transcribed spacer1 (ITS1) and Kinetopast (KDNA) genes. The results revealed that 43% of cases were positive by Microscopic examination while 16% by culture and 91% by R.T- PCR positive for kDNA gene , 60% for (ITS1) gene , it was found , 62% were typed as L. tropica and 38% of isolates were typed as L.major . Highly Significant (P<0.01) correlation was observed between diagnosis methods.